Metastable phase-separated droplet generation and long-time DNA enrichment by laser-induced Soret effect - Mika Kobayashi; Yoshihiro Minagawa; Hiroyuki Noji (Communications Chemistry)
Abstract Spatiotemporally controlled laser-induced phase separation (LIPS) offers unique research avenues and has potential for biological and biomedical applications. However, LIPS conditions often have drawbacks for practical use, which limit their applications. For instance, LIPS droplets are unstable and diminish after the laser is terminated. Here, we developed a novel LIPS method using laser-induced Soret effect with a simple setup to solve these problems. We generate liquid-liquid phase-separated (LLPS) droplets using LIPS in an aqueous two-phase system (ATPS) of dextran (DEX) and polyethylene glycol (PEG). When DEX-rich droplets were generated in the DEX/PEG mix on the phase boundary, the droplets showed unprecedently high longevity; the DEX droplets were retained over 48 h. This counterintuitive behaviour suggests that the droplet is in an unknown metastable state. By exploiting the capability of DEX-rich droplets to enrich nucleic acid polymers, we achieved stable DNA enrichment in LIPS DEX droplets with a high enrichment factor of 1400 ± 400. Further, we patterned DNA-carrying DEX-rich droplets into a designed structure to demonstrate the stability and spatiotemporal controllability of DEX-rich droplet formation. This is the first report for LIPS droplet generation in a DEX/PEG system, opening new avenues for biological and medical applications of LIPS.